THE MIGRATION PHENOMENON : BELONGS TO QUALITY OF PLACE AND HAPPINESS - Fresiani, Anggun (Program Studi Perencanaan Wilayah dan Kota, Fakultas Teknik, Universitas Semarang, 2024)
Typically, migration is carried out to fulfill life goals and occurs across every generation, hence its importance in sustainable development. However, there exists an opposing phenomenon between the number of in-out migration and the Happiness Index. This research analyze the correlation of migration, place quality, and happiness as a life goals. This research gathers primary data using Stratified Multiple Random Sampling method and analyzed the correlation and influence using SPSS. The differences in correlation results among variables were significant, where Yogyakarta City had positive correlations with migration and some components of place quality; some components of place quality and happiness. Meanwhile, Bekasi Region showed negative correlations with migration and happiness. Furthermore, migration in both locations was influenced by some components of quality of place and some dimensions of happiness. The aggregate results can depict spatial needs priority in planning, which can act as a stimulus for the distribution of migration.